Characterization of the enzymatic and multifunctional properties of Acinetobacter baumannii erythrose-4-phosphate dehydrogenase (E4PDH). (February 2023) - Nimma, Ramesh; Kumar, Ajay; Gani, Zahid; Gahlawat, Anuj; Dilawari, Rahul; Rohilla, Rajesh Kumar; Kumbhar, Hemangi; Garg, Prabha; Chopra, Sidharth; Raje, Manoj; Iyengar Raje, Chaaya
Abstract: Infections due to Acinetobacter baumannii (A. baumannii) are rapidly increasing worldwide and consequently therapeutic options for treatment are limited. The emergence of multi drug resistant (MDR) strains has rendered available antibiotics ineffective, necessitating the urgent discovery of new drugs and drug targets. The vitamin B6 biosynthetic pathway has been considered as a potential antibacterial drug target but it is as yet uncharacterized for A. baumannii. In the current work, we have carried out in silico and biochemical characterization of Erythrose-4-phosphate dehydrogenase (E4PDH) (EC 1.2.1.72). This enzyme catalyzes the first step in the deoxyxylulose-5-phosphate (DXP) dependent Vitamin B6 biosynthetic pathway i.e. the conversion of d -erythrose-4-phosphate (E4P) to 4-Phosphoerythronate. E4PDH also possesses an additional activity whereby it can catalyze the conversion of Glyceraldehyde-3-phosphate (G3P) to 1, 3 bisphosphoglycerate (1, 3BPG). Our studies have revealed that this enzyme exhibits an alternate moonlighting function as a cell surface receptor for the human iron transport proteins transferrin (Tf) and lactoferrin (Lf). The present work reports the internalization of Tf and consequent iron acquisition as an alternate strategy for iron acquisition. Given its essential role in two crucial pathways i.e. metabolism and iron acquisition, A. baumannii E4PDH may play a vital role in bacterial pathogenesis. Highlights: The study identifies the presence of the DXP-dependent pathway Vitamin B6 synthesis in A.baumannii. Cloning and characterization of E4PDH was carried out using biochemical and in silico methods. E4PDH demonstrated dual substrate specificity, alongwith variable sensitivity to inhibitors H202 and Ethyl bromo pyruvate (EBP). Significant differences were observed in the catalytic activity of the enzyme as compared to the E.coli homolog-. E4PDH was found was identified as a cell surface receptor for human iron transport proteins-Transferrin and Lactoferrin revealing the biochemical and moonlighting function of E4PDH.